Pathogenicity of different fungal entomopathogens for the control of Aleurotrachelus socielis (Homoptera: Aleyrodidae) under greenhouse conditions - ALEÁN-C., IRINA; MORALES-R., ANUAR; HOLGUÍN-A., CLAUDIA MARÍA; BELLOTTl, ANTHONY C. (Revista Colombiana de Entomología, 2004)
A complex of eight whitefly species associated with cassava exists in Colombia. The predominant species Aleurotrachelus socialis Bondar, which constitutes 92% of the total population and causes yield losses of up to 79% in field experiments. In order to offer cassava  growers an alternative to chemical control to reduce costs and environmental degradation we assessed the pathogenicity of various strains of the entomopathogenic fungí Beauveria bassiana (Bálsamo) Vuillemin, Verticillium lecanii (Zímm.) Viegas and Paecilomyces fumosoroseus (Wize) Brown &'. Smith on different nymphal stages and eggs of A. socialis in order to determine the most susceptible developmental stage, select the most promising isolate and identify the lethal concentration (CL50) . We also evaluated different commercial formulation of entomopathogenic fungí on the most susceptible developmental stage of A. socialis. We observed differences in mortality between the fungal species used and the control treatment. The V. lecenii strain CIAT 215 was selected as the most promising because it presented the highest mortality to A. socialis developmental stages (67,3%). The most susceptible stage were eggs close to hatching. We tested the strain CIAT 215 in seven  concentrations on this stage and  determinated that the CL was  l,4x107 conidia/ml with a confidence interval of 3.6xl05-1.5x109conidia/ml. The evaluated commercial formulations caused mortality of less than 50%, however, they were still statistically different than the control treatment.